2017
DOI: 10.1162/jocn_a_01102
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Sequential Modulations of Control Processes in Arithmetic Strategies: A Magnetoencephalography Study

Abstract: In a wide variety of cognitive domains, performance is determined by the selection and execution of cognitive strategies to solve problems. We used magnetoencephalography to identify the brain regions involved and specify the time course of dynamic modulations of executive control processes during strategy execution. Participants performed a computational estimation task in which they were instructed to execute a poorer or better strategy to estimate results of two-digit multiplication problems. When participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 75 publications
5
25
0
Order By: Relevance
“…Our results are in line with previous studies (e.g., Hinault, Badier, Baillet, & Lemaire, 2017;Taillan et al, 2015), which show that cognitive control processes modulate strategy selection. According to Botvinick (2007), conflict monitoring biases behavior towards cognitively efficient tasks and strategies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with previous studies (e.g., Hinault, Badier, Baillet, & Lemaire, 2017;Taillan et al, 2015), which show that cognitive control processes modulate strategy selection. According to Botvinick (2007), conflict monitoring biases behavior towards cognitively efficient tasks and strategies.…”
Section: Discussionsupporting
confidence: 93%
“…Taillan et al believe the AG reflects the participants' use of a heuristic that helps in selecting the better strategy in the computational estimation task. Also, the ACC and DLPFC were previously observed in conflict tasks (e.g., Botvinick et al, 2001Botvinick et al, , 2004Braver, 2012;Braver et al, 2009;Kerns, 2004Kerns, , 2006, the authors therefore interpreted the results as reflecting response conflict detection and resolution and suggested that executive control processes are necessary during strategy selection.Another study has shown that cognitive control is influenced by sequential modulations of arithmetic strategies (Hinault, Badier, Baillet, & Lemaire, 2017). The results of this study have demonstrated that the efficiency of strategy selection and execution differs depending on the previous item.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Presumably, the performance-contingent feedback enhanced conflict-driven control processes operating at a local level. This boost in CC might stem from changes in specific motivation processes (Van Steenbergen, Band, & Hommel, 2015), especially if the previous trial was conflict-related (Hinault, Badier, Baillet, & Lemaire, 2017). Interestingly, in high conflict frequency, the previous and current congruency also interacted with one another, revealing a systematic slowing done for cC relative to iC trials.…”
Section: Discussionmentioning
confidence: 94%
“…Further, it has even been proposed that the more efficient conflict processing usually observed after incongruent trials compared with congruent ones might actually reflect in part the proactive preparation occurring from one trial onto the next one (Duthoo, abrahamse, Braem, Boehler, & Notebaert, 2014;Hinault, Badier, Baillet, & Lemaire, 2017). Therefore, proactive control likely modulates conflict-driven adaptive control, in the sense that it is probably shaped by specific preparatory processes which are based on specific expectations (Gratton et al, 1992), or through activating processes that anticipate conflict and are meant to 5 reduce interference (Burgess, & Braver, 2010), or perhaps its negative or aversive nature (Dreisbach & Fischer, 2012).…”
Section: Introductionmentioning
confidence: 99%